Conductas ideales o ideales de conducta - Zamora Acevedo, José Miguel (2017)
This paper deals with the ideal of conduct of judges. This reflection is developed on the basis of an examination of the ethical dimension, where the government of the judge’s actions takes place. The overall objective of these notes is to show the inconvenience of a society governed by emotional states, conduct, and desires to seek justice, which entails the establishment of desiderative thinking, in the figure of the legal operator.